WORKPLACE ECO-FRIENDLINESS - Protasenko, O.; Ivashura, A. (Municipal economy of cities. Series: «Economy science», 2023)
The problem of assessing the workplace eco-friendliness is considered. Based on existing developments in ecology, labour protection, ergonomics, and life safety, a definition of the concept of workplace eco-friendliness is proposed. A method for assessing workplace eco-friendliness was developed, which is based on an adapted version of the Fine-Kinney method.